Development of an automated glove for post stroke hand rehabilitation and assistance - Adittya, Ashraf Shafayet; Irfa Chowdhury, MD Fahin Fuad; Islam, Sajidul; Ahnaf, Salman (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.